Employee deviant behavior: role of culture and organizational relevant support. Issue 2 (8th July 2019) - Kalemci, R. Arzu; Kalemci-Tuzun, Ipek; Ozkan-Canbolat, Ela
Abstract : Purpose: The purpose of this paper is to increase the knowledge and understanding of organizational and supervisory support in the context of employee deviant workplace behavior (DWB) by examining the potential associations of employees' cultural value orientations. This paper aims to: clarify DWB; review perceived organizational support (POS) and perceived supervisory support (PSS); discuss the meaning of employees' cultural value orientations (individualism–collectivism, power distance and paternalism); use the fuzzy logic model to analyze relationships between DWB and POS, as well as PSS and employees' cultural value orientations. Design/methodology/approach: This research applies a fuzzy-set qualitative comparative analysis. Findings: The results show the role of employee perceived organizational and supervisory support and cultural dimension (power distance and paternalism) configurations on employee DWB. Originality/value: The main originality of this study is to further increase the understanding of organizational and supervisory support in the context of employee DWB by examining the potential associations of employees' cultural value orientations. This study extends the previous research by providing evidence that organizational and supervisory support influences employees' DWB.